2015
DOI: 10.1002/aur.1570
|View full text |Cite
|
Sign up to set email alerts
|

Human Inducible Pluripotent Stem Cells and Autism Spectrum Disorder: Emerging Technologies

Abstract: Autism Spectrum Disorder (ASD) is a behaviorally defined neurodevelopmental condition. Symptoms of ASD cover the spectrum from mild qualitative differences in social interaction to severe communication and social and behavioral challenges that require lifelong support. Attempts at understanding the pathophysiology of ASD have been hampered by a multifactorial etiology that stretches the limits of current behavioral and cell based models. Recent progress has implicated numerous autism-risk genes but efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 193 publications
(235 reference statements)
0
14
0
Order By: Relevance
“…Although the iPSC field is in early development, the potential to model aspects of ASC using human neurons is promising. 128 The ability to develop human cortical tissue in vitro presents scientists with multiple new options to design experiments that integrate results from both rodent and clinical studies that will result in greater clinical translatability.…”
Section: Asc Therapeutic Targets In Ipsc-derived Neuronal Culturesmentioning
confidence: 99%
“…Although the iPSC field is in early development, the potential to model aspects of ASC using human neurons is promising. 128 The ability to develop human cortical tissue in vitro presents scientists with multiple new options to design experiments that integrate results from both rodent and clinical studies that will result in greater clinical translatability.…”
Section: Asc Therapeutic Targets In Ipsc-derived Neuronal Culturesmentioning
confidence: 99%
“…Indeed, brain imaging studies from individuals with ASD and anatomical measurements of neuronal structure in post-mortem tissues exhibit differences in neuronal connectivity derived from the disruption of neurite outgrowth, synapse formation and stabilization (Raymond et al, 1996; Hutsler and Zhang, 2010; Penzes et al, 2011). Studies of human induced pluripotent stem cells (iPSCs) derived from people with ASD also have identified defects of neuronal structure (Habela et al, 2015; Nestor et al, 2015). Genome-wide association studies on individuals with ASD and their families revealed several risk genes that may be the common molecular targets in autism (Bucan et al, 2009; Glessner et al, 2009; Hussman et al, 2011; O’Roak et al, 2011, 2012a; Buxbaum et al, 2012, 2014; Sanders et al, 2012; Shi et al, 2013; Stamou et al, 2013; Yu et al, 2013; An et al, 2014; Brett et al, 2014; Cukier et al, 2014; De Rubeis et al, 2014; Iossifov et al, 2014; McGee et al, 2014; Pinto et al, 2014; Ronemus et al, 2014; Toma et al, 2014; Yuen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, iPSC models not only enable the examination of molecular interactions and the fate of cells, but also provide the possibility to make investigations within the context of more complex systems and biochemical processes 17 . Due to the electrophysiological, gene expression, and other cell-based quantitative studies that can be performed on iPSC models, efforts to develop comprehensive models for autism, which have so far been slow in progress, can gain momentum 18 .…”
Section: Ipscs In Autism Modellingmentioning
confidence: 99%